K-(-6)=-33

Simple and best practice solution for K-(-6)=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K-(-6)=-33 equation:


Simplifying
K + -1(-6) = -33

Multiply -1 * -6
K + 6 = -33

Reorder the terms:
6 + K = -33

Solving
6 + K = -33

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + K = -33 + -6

Combine like terms: 6 + -6 = 0
0 + K = -33 + -6
K = -33 + -6

Combine like terms: -33 + -6 = -39
K = -39

Simplifying
K = -39

See similar equations:

| x+0.5x+0.25x+1=100 | | x+(2x-15)=150 | | x+0.5x+0.75x+1=100 | | 6x-2=64(2x) | | 5+2+x=9 | | 4x=12-x | | sin*2*t= | | 3y+3=6(y+1) | | (2x+5)+(2x+2)=4(x-1)+9 | | (5-2x)(2x+1)=4x^2-25 | | (y+1)(y-2)= | | 3m/7=9 | | (5-2x)(2x+7)=4x^2-25 | | (6x+4)-(-6x+5)= | | Y(5-2)=52 | | (x+12)*4=90-2x | | 4x^4-2x^3+7x^2+3x+9=0 | | 2r-.75=1 | | (2x+1)+(-1x+9)= | | 4(x+12)=90-2x | | 4(4+12)=90-2x | | 22=6p+4 | | a-4x=14 | | 5x-2(-2x+1)=2(2x+15) | | 10x^2-135=25 | | -6(x+1)-12=28+8 | | 22=6p+4p | | 4(-5)+2=x+3 | | 44-3x=9-8x | | 3(-2x-7)=3(-9x+5) | | 64-5x=31x+24 | | 0.3333(2x-5)=3 |

Equations solver categories